COMPETITIVENESS ANALYSIS AND MARKETING STRATEGIES JAVA COFFEE GROUND COFFEE (EMPIRICAL STUDY IN UD. NURI SUMBERWRINGIN, BONDOWOSO) - Fatmawati, Fatmawati; Yudhia Kurniawan, Bagus Putu; Suryadi, Ujang (Jurnal Pertanian, 2019)
Bondowoso is one of the coffee planting centers in East Java with special taste (specialties) Java Coffee. The local government gives fully support to create quality processed products that can increase revenue and sales volume of ground coffee that still under ‘ose coffee’ sales. It needs study of the competitiveness of Bondowoso processed ground coffee ‘java coffee’ specialties products to assess whether the business is feasible to be developed economically or not. This study used Analysis method using Policy Analysis Matrix. For an alternative marketing strategy used an Internal Factor Evaluation (IFE) matrix, External Factor Evaluation (EFE Internal-External (IE) and SWOT, priority marketing strategy with Analytical Hierarchy Process (AHP). The purposes of research are: 1) Knowing the competitiveness of ground coffee java coffee UD. Nuri, 2) Determining the right strategy to improve the competitiveness of ground coffee java coffee UD.Nuri. The data analysis methods used was IFE and EFE Matrices. Alternative business development strategy used IE and SWOT matrices, for business development strategy priority used AHP. Ground coffee java coffee has a comparative advantage and competitive with coefficient DRC = 0.052 and PCR = 0.489. Ground coffee java coffee agribusiness position is in quadrant I, the right strategy to improve the ground coffee UD. Nuri Bondowoso is conducting an effective promotion through social media (digital marketing).